SEMIOTIC ANALYSIS OF THE FILM POSTER "HOME SWEET LOAN" - Waltz, Hilmi Hasbiya Zahrani; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Film posters as visual media have a very important role. Apart from being a promotional medium that aims to attract the attention of the audience or potential audience, film posters are also very important in conveying the content of the message or meaning contained in the content of the film. This study aims to analyze the meaning contained in the movie poster "Home Sweet Loan" with Ferdinand de Saussure's semiotic approach which emphasizes the relationship between signifier and signified in the process of forming meaning. This study uses a qualitative descriptive research method to describe the visual elements contained in the film poster. The data collection techniques in this study include visual documentation in digital form and visual communication theory. The data analysis technique to be used is Ferdinand de Saussure's semiotics. The results of the study show that Ferdinand de Saussure's semiotic theory can be used to show the meaning contained in the movie poster "Home Sweet Loan".